Latihan Range of Motion Berpengaruh Terhadap Mobilitas Fisik pada Lansia di Balai Pelayanan Sosial Tresna Werdha Unit Abiyoso Yogyakarta - Hermina Desiane Hastini Uda; Muflih Muflih; Thomas Aquino Erjinyuare Amigo (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2016)
The increasing of Life Expectancy has raised the population of the elderly. The highest population number of elderly in Indonesia can be found in Yogyakarta Special Region with 13.05%. The increasing life expectancy brings normal and pathological changes in the elderly as it relates to aging process in various systems. Normal changes are seen in the musculoskeletal system that is in the complete loss of muscle at the age of 80 (30%-50%). The changes can be found in such cases as rheumatoid arthritis, osteoarthritis, and osteoporosis. Such changes have made the elderly susceptible to hindrances of physical mobility which can be treated by giving range of motion (ROM) Exercises. The purpose of study to find out the effect of ROM Exercises against physical mobility for the elderly in Center for Social Services, Tresna Werdha, Unit Abiyoso Yogyakarta. This study was a qualitative research with an action research design. A purposive sampling method was used to collect the data from 5 respondents. Results: Physical mobility in elderly consists of five themes, namely range of motion, muscle strength, comfort, posture, and movement. ROM exercises provides changes in the ROM, comfort, and movement, but no change in the muscle strength and posture. Changes in the range of motion are found in the increased level of the range of motion which is seen in neck area and in reduced joint stiffness. Changes in comfort are seen in a feeling of happiness and less pain; yet, shortness of breath is not reduced. Changes in movement, which are different for every elderly, can be seen in increased gait speed, increased comfort which is the effect of fine motor skills, and decreased trembling. Conclusion: Some ROM exercises show effects on the physical mobility of the elderly. The effects can be traced from increased range of motion, comfort, and gait speed. Yet, the elderly’s posture and muscle strength do not experience any changes.